Deep Learning in Islamic Religious Education: Optimizing a Deeper Learning Process - Saridudin, Saridudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article analyzes the application of the Deep Learning approach in Islamic Religious Education learning. Along with the rapid development of information and communication technology, especially in artificial intelligence, deep learning offers solutions to improve the quality of education, including in Islamic Religious Education learning. The deep learning approach can be used in several aspects, including personalizing learning materials, adapting learning models that are based on student characteristics, and providing in-depth data analysis that can be used to assess student understanding and learning progress. The Islamic Religious Education learning process is expected to be more effective, efficient, and interactive through the deep learning approach. This paper identifies various ways the deep learning approach can be implemented in Islamic Religious Education learning, including in several subjects such as Fiqh, Qur'an Hadith, History of Islamic Culture and Aqidah Akhlak. The findings of this study indicate that implementing the deep learning approach in Islamic Religious Education learning can enrich students' learning experiences, accelerate their understanding of Islamic Religious Education concepts, and provide a deeper experience of Islam for students. Thus, the deep learning approach not only plays a role in accelerating the transfer of knowledge but also enriches the quality of understanding of Islamic Religious Teachings more holistically.